Упростите: (1/(a-b)-(a^2+ab)/(a^3-b^3))/((b^2)/(a^2+ab+b^2))

0 голосов
21 просмотров

Упростите:
(1/(a-b)-(a^2+ab)/(a^3-b^3))/((b^2)/(a^2+ab+b^2))


Алгебра (226 баллов) | 21 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:

(\frac{1}{a-b}-\frac{a^2+ab}{a^3-b^3}):\frac{b^2}{a^2+ab+b^2}=(\frac{1}{a-b}-\frac{a^2+ab}{(a-b)(a^2+ab+b^2)}):\frac{b^2}{a^2+ab+b^2}=(\frac{a^2+ab+b^2}{(a-b)(a^2+ab+b^2)}-\frac{a^2+ab}{(a-b)(a^2+ab+b^2)}):\frac{b^2}{a^2+ab+b^2}=(\frac{a^2+ab+b^2-a^2-ab}{(a-b)(a^2+ab+b^2)}):\frac{b^2}{a^2+ab+b^2}=\frac{b^2}{(a-b)(a^2+ab+b^2)}}\cdot\frac{a^2+ab+b^2}{b^2}=\frac{b^2(a^2+ab+b^2)}{(a-b)(a^2+ab+b^2)b^2}}=\frac{1}{a-b}}

(8.8k баллов)
0 голосов

Решите задачу:

(\frac{1}{a-b}-\frac{a^2+ab}{a^3-b^3}):\frac{b^2}{a^2+ab+b^2}=\frac{a^2+ab+b^2-a^2-ab}{(a-b)(a^2+ab+b^2)}\cdot \frac{a^2+ab+b^2}{b^2}=\\\\=\frac{b^2}{(a-b)(a^2+ab+b^2)}\cdot \frac{a^2+ab+b^2}{b^2}=\frac{1}{a-b}

(835k баллов)